2004
DOI: 10.1111/j.1600-6143.2004.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Assessment for Pancreas Transplants

Abstract: 90.5%). Up to one-third of recipient deaths after posttransplant day 90 were not related to the transplant procedure itself. Multivariate analyses showed that the overall mortality in all three categories was not increased after transplantation (for SPK recipients only, it was significantly decreased). In summary, the mortality for solitary pancreas transplant recipients is not higher than for wait-listed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
194
1
15

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(220 citation statements)
references
References 28 publications
(39 reference statements)
10
194
1
15
Order By: Relevance
“…Both transplantation options can be conducted alone or in combination with a kidney. Whereas simultaneous pancreaskidney (SPK) transplantation is an intervention with proven benefits in terms of survival (4), conflicting results in pancreas transplantation alone have been published (5,6).…”
mentioning
confidence: 99%
“…Both transplantation options can be conducted alone or in combination with a kidney. Whereas simultaneous pancreaskidney (SPK) transplantation is an intervention with proven benefits in terms of survival (4), conflicting results in pancreas transplantation alone have been published (5,6).…”
mentioning
confidence: 99%
“…Estes dados parecem ser, entre outros, o resultado de avanços nas técnicas cirúrgicas e nos imunossupressores. Em relação a anos de vida ganhos em pacientes submetidos ao transplante isolado de pâncreas e pâncreas após rim, os estudos não mostraram vantagens em relação aos pacientes que permaneceram na lista de espera (26,27).…”
Section: Esquema De Imunossupressãounclassified
“…This recommendation is the result of the beneficial effects observed in terms of quality of life and survival after kidneypancreas transplantation into patients suffering for DMT1 (Reddy et al, 2003). However since the procedure of pancreas transplantation has an high incidence of mortality and morbidity (Gruessner et al, 2004) it can be proposed only to selected population of patients candidate to kidney transplantation for diabetic nephropathy. In this the European Trial of Immunosuppression in Simultaneous Pancreas Kidney Transplantation (EUROSPK) study group reported that repeated laparotomies in the first 3 months after transplantation were performed in 35% of all the patients.…”
Section: Combined Kidney-islet Transplantation: Indicationsmentioning
confidence: 99%